Associations of five dietary indices with metabolic dysfunction-associated steatotic liver disease and liver fibrosis among the United States population - Xu, Min; Zhan, Yamei; Gao, Guohui; Zhu, Li; Wu, Tong; Xin, Guijie (Frontiers in Nutrition, 2024)
Background and aims The role of dietary factors in metabolic dysfunction-associated steatotic liver disease (MASLD)—which represents a new definition of liver steatosis and metabolic dysfunction— remains unclear. This study aimed to explore the relationships between dietary indices and MASLD. Methods We analyzed data from the United States National Health and Nutrition Examination Survey (NHANES) 2017–2020 cycle, including 4,690 participants with complete vibration-controlled transient elastography (VCTE) data. Multivariate logistic regression models adjusted for covariates were used to assess the association between dietary indices, MASLD, and MASLD-associated liver fibrosis (MASLD-LF). Restricted cubic spline (RCS) models and subgroup analyses were also performed. Results The Alternative Healthy Eating Index (AHEI), Healthy Eating Index-2020 (HEI-2020), Dietary Approaches to Stop Hypertension Index (DASHI), and Mediterranean Diet Index (MEDI) were found to be negatively associated with MASLD risk, while the Dietary Inflammatory Index (DII) had a positive association. The highest quartile of MEDI was linked to a 44% reduction in MASLD risk [Q1 vs. Q4 odds ratio (OR): 0.56; 95% confidence interval (CI): 0.34–0.94, P for trend: 0.012]. DASHI was uniquely associated with a reduced risk of MASLD-LF (continuous OR: 0.79; 95% CI: 0.64–0.97; p for trend: 0.003). Our RCS curves indicated a nonlinear association with DASHI-MASLD (p-overall: 0.0001, p-nonlinear: 0.0066). Subgroup analyses showed robust associations among the non-Hispanic White and highly educated populations. Conclusion Specific dietary patterns were associated with reduced risks of MASLD and MASLD-LF. The DASHI, in particular, showed a significant protective effect against MASLD-LF. These findings suggest potential dietary interventions for managing MASLD and MASLD-LF, although large-scale randomized controlled trials are warranted to validate these findings.